Translation and Continuity of Tradition: An Ongoing Dialogue in Aotearoa (New Zealand) - Jaspreet Kaur (INTBAU Spain, 2021)
Though short, Aotearoa/New Zealand’s history is rich and holds an abundance of knowledge preserved in the form of songs, beliefs, practices, and narratives that inform this country’s unique place in the world as well as the identity of its people. This paper observes that with migratory history and a heritage of colonization, the people of Aotearoa/New Zealand express three identities: indigenous, colonial and migrant, all with a claim to appropriate representation in the country’s built fabric. It discusses the current state of knowledge by looking at the history and architectural tradition manifested in Auckland, the largest and fastest-growing city in Aotearoa. It adds that further research is required to understand and develop an appropriate methodology to address Auckland’s growing multiculturalism, which lacks adequate expression.